Synthesis and biological activity of imidazole phenazine derivatives as potential inhibitors for NS2B-NS3 dengue protease - Nur Sarah Dyana Khalili; Muhammad Hidhir Khawory; Nurul Hanim Salin; Iffah Izzati Zakaria; Maywan Hariono; Andrey A. Mikhaylov; Ezatul Ezleen Kamarulzaman; Habibah A Wahab; Unang Supratman; Mohamad Nurul Azmi (Heliyon, 2024)
A series of new imidazole-phenazine derivatives were synthesized via a two-step process. The condensation of 2,3-diaminophenazine and benzaldehyde derivatives proceeds with intermediate formation of an aniline Schiff base, which undergoes subsequent cyclodehydrogenation in situ. The structures of the synthesized compounds were characterized by 1D and 2D NMR, FTIR and HRMS. A total of thirteen imidazole phenazine derivatives were synthesized and validated for their inhibitory activity as anti-dengue agents by an in vitro DENV2 NS2B-NS3 protease assay using a fluorogenic Boc-Gly-Arg-Arg-AMC substrate. Two para-substituted imidazole phenazines, 3e and 3k, were found to be promising lead molecules for novel NS2B-NS3 protease inhibitors with IC50 of 54.8 μM and 71.9 μM, respectively, compared to quercetin as a control (IC50 104.8 μM). The in silico study was performed using AutoDock Vina to identify the binding energy and conformation of 3e and 3k with the active site of the DENV2 NS2B-NS3 protease Wichapong model. The results indicate better binding properties of 3e and 3k with calculated binding energies of −8.5 and −8.4 kcal mol−1, respectively, compared to the binding energy of quercetin of −7.2 kcal mol−1, which corroborates well with the experimental observations.